The Usage of 'Otsukare' among Japanese Students - Santiar, Lea; Dewangga, Jascha (Universitas Negeri Semarang, 2021)
Greetings are one of the keys to strike a conversation. The relationship between the speakers could be measured through the greetings used. Therefore understanding greeting usage is necessary for maintaining an interpersonal relationship. Nevertheless, there seems to be a difference between greetings thought within Japanese textbooks and greetings in daily usage. Thus, this study will discuss the usage of ‘otsukare’ in Japan, especially amongst Japanese university students. The textbook